1953
DOI: 10.1001/archneurpsyc.1953.02320250070007
|View full text |Cite
|
Sign up to set email alerts
|

Familial Ocular Myopathy and External Ophthalmoplegia

Abstract: INVOLVEMENT of the oculomotor muscles in the course of a generalized muscular dystrophy is not common. Even more unusual is a dystrophy limited to the ocular muscles without evidence of muscular involvement elsewhere in the body. A few such cases have been described by Kiloh and Nevin.1 We are reporting the clinical and pathologic observations on a patient who had this syndrome, and also the clinical findings in four members of his family. These cases form an entity, little recognized clinically, and in addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1959
1959
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Histology of biopsies and post-mortem material [6][7][8][9][10] and electromyographic studies [11,12] confirmed this conclusion.…”
Section: Introductionmentioning
confidence: 82%
“…Histology of biopsies and post-mortem material [6][7][8][9][10] and electromyographic studies [11,12] confirmed this conclusion.…”
Section: Introductionmentioning
confidence: 82%
“…In 1868 a German ophthalmologist reported the rst case of PEO, attributing the clinical manifestations to disorders of the ocular nerves, about 100 years before description of the rst mitochondrial disorder with the introduction in the medical eld of this new group of diseases [16] and the later report of the rst pathogenic mtDNA variants [17,18], that ushered MDs in the nowadays molecular era. Myopathic etiology of PEO was documented in the mid-1950s [19][20][21][22]. In 1958, Kearns and Sayre reported a clinically distinct form of PEO, KSS, characterized by multisystemic involvement [11].…”
Section: Discussionmentioning
confidence: 99%
“…Dysphagia was prominent in four patients (8,22,27,28), and dysarthria occurred in three (8,22,28). Weakness and wasting of face and shoulder girdle muscles was encountered twice (6,9). A variety of other neurological abnormali¬ ties occurred in nine cases ( (9) and is described with the case history below.…”
mentioning
confidence: 97%
“…Weakness and wasting of face and shoulder girdle muscles was encountered twice (6,9). A variety of other neurological abnormali¬ ties occurred in nine cases ( (9) and is described with the case history below. Five biopsies of clinically affected deltoid or gastrocnemius muscles showed myopathie changes (4,8,17,18,27).…”
mentioning
confidence: 99%